Nutrient availability and acid erosion determine the early colonization of limestone by lithobiontic microorganisms - Chen, Jin; Zhao, Qing; Li, Fangbing; Zhao, Xiangwei; Wang, Yang; Zhang, Limin; Liu, Jinan; Yan, Lingbin; Yu, Lifei (Frontiers in Microbiology, 2023)
Microorganisms, including the pioneer microorganisms that play a role in the early colonization of rock, are extremely important biological factors in rock deterioration. The interaction of microorganisms with limestone leads to biodeterioration, accelerates soil formation, and plays an important role in the restoration of degraded ecosystems that cannot be ignored. However, the process of microbial colonization of sterile limestone in the early stages of ecological succession is unclear, as are the factors that affect the colonization. Acid erosion (both organic and inorganic), nutrient availability, and water availability are thought to be key factors affecting the colonization of lithobiontic microorganisms. In this study, organic acid (Oa), inorganic acid (Ia), inorganic acid + nutrient solution (Ia+Nut), nutrient solution (Nut), and rain shade (RS) treatments were applied to sterilized limestone, and the interaction between microorganisms and limestone was investigated using high-throughput sequencing techniques to assess the microorganisms on the limestone after 60 days of natural placement. The results were as follows: (1) The abundance of fungi was higher than that of bacteria in the early colonization of limestone, and the dominant bacterial phyla were Proteobacteria, Bacteroidota, and Actinobacteriota, while the dominant fungal phyla were Ascomycota, Basidiomycota, and Chytridiomycota. (2) Acid erosion and nutrient availability shaped different microbial communities in different ways, with bacteria being more sensitive to the environmental stresses than fungi, and the higher the acidity (Ia and Oa)/nutrient concentration, the greater the differences in microbial communities compared to the control (based on principal coordinate analysis). (3) Fungal communities were highly resistant to environmental stress and competitive, while bacterial communities were highly resilient to environmental stress and stable. In conclusion, our results indicate that limestone exhibits high bioreceptivity and can be rapidly colonized by microorganisms within 60 days in its natural environment, and both nutrient availability and acid erosion of limestone are important determinants of early microbial colonization.